Solubility and dissolution studies of tibolone polymorphs - Rudy Bonfilio; Marília Cristina Oliveira Souza; Jockastta Silva Leal; Olímpia Maria Martins Santos Viana; Antônio Carlos Doriguetto; Magali Benjamin de Araújo (Universidade de São Paulo, 2018)
ABSTRACT Different solid forms of an active pharmaceutical ingredient can have distinct chemical and physical characteristics. In this work, we studied the solubility and dissolution properties of the described tibolone polymorphic forms (I and II). Both forms were successively recrystallized and characterized by powder X-ray diffraction and attenuated total reflection infrared spectroscopy. Equilibrium solubility and dissolution profiles were performed for both forms. Solubility studies demonstrated that form II is statistically more soluble in water, 0.01 mol L-1 HCl and pH 4.5 acetate buffer. The solubility of forms I and II were explained in terms of crystal packing. Dissolution tests of tablets showed a lower release of polymorphic form II than form I from tablets. The results showed an impact of polymorphism on the quality of tibolone tablets and suggest that tibolone forms I and II can show distinct interactions with pharmaceutical excipients used in tablets. Therefore, only form I is acceptable for the preparation of tablet forms. Based on our results, we propose the quality control on tibolone raw materials using X-ray diffraction analysis and attenuated total reflection infrared spectroscopy.